Cold chain logistics: The case of Turkish Airlines vaccine distribution - Sercan Demir; Ersin Aktas; Turan Paksoy (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: The world is going through unprecedented times since the beginning of the COVID-19 pandemic. Billions of people will be vaccinated in the next few years. This mass vaccination effort requires setting up complex cold chain organizations and meticulous coordination of distribution networks. Keeping coronavirus vaccines at appropriate temperatures during the distribution process is not easy; however, it is one of the key factors battling against COVID-19. The purpose of this paper is to discuss and identify the essential logistics capabilities of cold storage and logistics service providers during the COVID-19 vaccine distribution. Methodology: First, we identify the prominent risks that cold chain distributors encounter during vaccine transportation by conducting an in-depth literature review and an interview with the vice president of one of the largest air cargo companies in the world. Then we discuss logistics capabilities for the mitigation of these risks. Finally, we explore the Turkish Cargo's cold chain footprint enlargement strategy during the pandemic. Findings: Cold chain logistics requires special attention to specific capabilities due to the nature of the cargoes being transported. On-time delivery time, special storage and transport equipment, and process monitoring ability are among the core capabilities for cold chain logistics service providers. Ensuring the reliable and effective distribution of temperature-sensitive vaccines is crucial since millions of lives depend on them. Originality: This study is one of the first papers investigating the cold chain capabilities of air cargo distributors during the COVID-19 pandemic.
urn:nbn:de:gbv:830-882.0161763; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Supply Chain Risk Management; Supply Chain Security